2020
DOI: 10.3390/cells9051136
|View full text |Cite
|
Sign up to set email alerts
|

PDPN Is Expressed in Various Types of Canine Tumors and Its Silencing Induces Apoptosis and Cell Cycle Arrest in Canine Malignant Melanoma

Abstract: Podoplanin (PDPN), a small transmembrane mucin-like glycoprotein, is ectopically expressed. It is also known to be linked with several aspects of tumor malignancy in some types of human tumors, including invasion, metastasis, and cancer stemness. However, there are few reports on the expression of dog PDPN (dPDPN) in canine tumors, and the association between dPDPN and tumor malignancy has not been elucidated. We identified that 11 out of 18 types of canine tumors expressed dPDPN. Furthermore, 80% of canine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…In this study, the reactivity and ADCC of P38Bf were evaluated using canine malignant melanoma cell lines. This study targets canine malignant melanoma because it was reported that 80% of canine malignant melanomas express dPDPN on tumor cells [ 18 , 45 ]. P38Bf clearly recognized endogenously expressed dPDPN on canine malignant melanoma cell lines and showed significant and dose-dependent ADCC activity on CMM2 at antibody concentrations of 1 and 10 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the reactivity and ADCC of P38Bf were evaluated using canine malignant melanoma cell lines. This study targets canine malignant melanoma because it was reported that 80% of canine malignant melanomas express dPDPN on tumor cells [ 18 , 45 ]. P38Bf clearly recognized endogenously expressed dPDPN on canine malignant melanoma cell lines and showed significant and dose-dependent ADCC activity on CMM2 at antibody concentrations of 1 and 10 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, PDPN has been reported to be overexpressed in various types of tumors, including squamous cell carcinoma [ 5 ], astrocytoma [ 6 ], malignant mesothelioma [ 7 ], hemangiosarcoma [ 8 ], osteosarcoma [ 9 ], germinoma [ 10 ], and cancer-associated fibroblasts (CAFs) [ 11 , 12 , 13 ]. Similar to humans, PDPN has been reported to be expressed in renal podocytes, alveolar epithelial cells, and lymphatic endothelial cells of dogs, and in various types of canine tumors, including malignant melanoma and squamous cell carcinoma [ 14 , 15 , 16 , 17 , 18 ]. Many reports have demonstrated that PDPN expressed on human and canine tumors is associated with tumor malignancy through the promotion of malignant proliferation and epithelial–mesenchymal transition (EMT), and that it promotes metastasis by enhancing tumor cell migration and platelet aggregation [ 1 , 2 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meningiomas are frequently positive for CD34, E‐cadherin, doublecortin and progesterone receptor (PR) 7,11‐13 . More recently, a high rate of somatostatin receptor type 2 (SSTR2) 14 and podoplanin 15 immunohistochemical expression have been reported in canine meningioma. However, any exclusive diagnostic specificity of these markers has not yet been confirmed in the dog.…”
Section: Introductionmentioning
confidence: 99%